Turkish Validity Reliability of the Pediatric Peripheral Intravenous Infiltration Scale and Its Adaptation to Newborns - KARAKOÇ, AYŞE (GALENOS YAYINCILIK, 2017)
Aim: The aim of this study is to determine the Turkish validity reliability and newborns' adaptation to Pediatric Peripheral Intravenous Infiltration Scale. Materials and Methods: This study is methodological and was conducted on 54 newborns with the simultaneous evaluation of two observers. Each infant was monitored 8 times with hourly observations from when the vein path was changed, and a total of 864 observational outcomes were assessed with scale. SPSS program was used for statistical evaluations. Results: A total of 54 newborns were taken into the study and the proportions of cases at each care level in neonatal intensive care unit were similar (level 1: 16 patients, level 2: 23 patients, level 3: 15 patients (p=0.348). The most commonly used fluid was found to be dextrose 10% in 63%, and total parenteral nutritional fluid in 26%. The newborns' postnatal age was median 3 days (minimum: 1, maximum: 27). A total of 864 observations were made for 8 hours and in the 35% (n=19) of 54 babies, the vein pathway was changed after the first observation. 69% of the infants whose vascular accesses were changed, were identified in the first stage (1 point), 25% in the second stage (2 points), and vascular accesses were renewed. The Krippendorff's alpha reliability coefficient showing the integration between the two evaluators was 1.00 (p< 0.001). This result shows full agreement between the two evaluators. Intra-class correlation coefficient showing reliability between measurements was r= 0.99 (p< 0.001). This coefficient also indicates that the measurements are highly reliable. Conclusion: Intravenous infiltration and extravasations are preventable complications in neonates and should be assessed with the aid of a scale at regular intervals. Pediatric Peripheral Intravenous Infiltration Scale can be used in newborns and also in Turkish.
Keywords: Infiltration; newborn; scale; EXTRAVASATION INJURIES; MANAGEMENT